PENGARUH KUALITAS LAYANAN DAN KEPUASAN PADA NIAT BELI ULANG PELANGGAN DI HOTEL INNA KUTA BEACH - Astawa, I Ketut (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2009)
This study aims to explain the influence of service quality and customer satisfaction on repurchase intention at Inna Kuta Beach Hotel The 'number of sample is 185 tourists consisting of 142 foreign and 43 domestic tourists. The data were collected by applying a convenience sampling technique and analyzed with Structural Equation Modeling using AMOS 4. 01 software. The result shows that service quality has no significant correlation on the repurchase intention, however, service quality has a significant and positive correlation on customer satisfaction. Customer satisfaction has a significant and positive correlation on repurchase intention and service quality has a positive correlation on repurchase intention indirectly through customer satisfaction which, in this case, functions as an intervening variable.